(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the competitive approach as a priority of the modern education system and its role in the State Education Standards (DTS). The theoretical foundations and practical significance of the formation of basic and subject competencies in students. The article also outlines the benefits of moving from knowledge-based traditional education to an education model that focuses on the application of skills and competencies in real-life situations.